Hubungan Lokasi Insersi Pemasangan Infus Dan Kejadian Flebitis (Systematic Literature Review) - Solehudin Solehudin; Astrid Novita; Risha Gustiani Hamzah (Universitas Katolik Widya Karya Malang, 2023)
Introduction : Central Line Associated Blood Stream Infection (CLABSI) or phlebitis is defined by the CDC as a bloodstream infection confirmed by laboratory results that occurs within 48 hours before developing into bacteremia, and is not associated with infection in other parts. Some research results conclude that several factors influence the occurrence of phlebitis, one of which is the selection of the insertion site. Purpose: to determine the effect of the insertion location of the infusion on the incidence of phlebitis. Design: Literature review method using Google Scholar and the Portal Garuda as databaseÂ (2018-2022). Method : keywords